An Impoliteness Strategies on Indonesian Presidential Candidate Debate 2024 - Damayanti, Wahyu Ajeng; Ambarwati, Rosita; Theresia Budi Sucihati (Universitas PGRI Madiun, 2024)
Impoliteness plays an important role when communicating. Many people may forget to act politely when communicating with others. This study aims to examine the type and function of impoliteness strategies in the Indonesian presidential candidates' 2024 debates. This research used a descriptive-qualitative approach. Data collection used were observation and documentation methods. Culpeper's theory (1996) and Culpeper's (2011) are used as the basis for analyzing impoliteness strategies. The results of this study are strategies of impoliteness were found in 37 data. Bald on record impoliteness was found as much as 1 (2.7%), positive impoliteness was found as much as 21 (56.8%), negative impoliteness was found as much as 11 (29.7%), and sarcasm or mock politeness was found as much as 4 (10.8%), while in the type of withhold politeness, no data was found. In this research, it was discovered that Indonesian presidential candidates predominantly employed the strategy of positive impoliteness during the debates. Furthermore, 23 data were found on the impoliteness function. Affective impoliteness was found in as many as 5 (21.8%) and coercive impoliteness was found in as many as 18 (78.2%), while in the entertaining impoliteness function no data was found.